Glutamine Availability Regulates the Development of Aging Mediated by mTOR Signaling and Autophagy - Zhou, Jiao; Chen, Honghan; Du, Jintao; Tai, Haoran; Han, Xiaojuan; Huang, Ning; Wang, Xiaobo; Gong, Hui; Yang, Mingyao; Xiao, Hengyi (Frontiers in Pharmacology, 2022)
Glutamine is a conditionally essential amino acid involved in energy production and redox homeostasis. Aging is commonly characterized by energy generation reduction and redox homeostasis dysfunction. Various aging-related diseases have been reported to be accompanied by glutamine exhaustion. Glutamine supplementation has been used as a nutritional therapy for patients and the elderly, although the mechanism by which glutamine availability affects aging remains elusive. Here, we show that chronic glutamine deprivation induces senescence in fibroblasts and aging in Drosophila melanogaster, while glutamine supplementation protects against oxidative stress-induced cellular senescence and rescues the D-galactose-prompted progeria phenotype in mice. Intriguingly, we found that long-term glutamine deprivation activates the Akt-mTOR pathway, together with the suppression of autolysosome function. However, the inhibition of the Akt-mTOR pathway effectively rescued the autophagy impairment and cellular senescence caused by glutamine deprivation. Collectively, our study demonstrates a novel interplay between glutamine availability and the aging process. Mechanistically, long-term glutamine deprivation could evoke mTOR pathway activation and autophagy impairment. These findings provide new insights into the connection between glutamine availability and the aging process.